Previous two lower segment caesarean section with placenta previa and placenta accreta woman with COVID-19 suspect: case report - Borse, Dhananajay; Mitra, Binay; Sharma, Aparna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
A pregnant woman with gravida 3, para 2, living 2 and gestational age of 37 weeks and 3 days was referred to a zonal hospital as previous two lower segment caesarean section (LSCS) term pregnancy with placenta previa for safe confinement with complaints of dry cough. She was admitted with a diagnosis of COVID-19 suspect. During her hospitalization, oxygen (O2) saturation was normal. On investigations her counts were normal. Patient was planned for elective LSCS. COVID-19 test i.e. real time-polymerase chain reaction (RTPCR) report was suspect and asked for repeat sampling. During elective LSCS, delivered single live female baby with intra operative findings of placenta previa with adherent placenta and permpartum hysterectomy was done for same. Uterus with placenta was sent for histopathological examination (HPE). During the surgery her oxygen concentration was normal. Her postoperative recovery was uneventful.